Poetry Aspect and Analysis That Contain In of Pearls and Stars By Heinrich Heine - Hakim, Dewa Bayu (LANTERN (Journal on English Language, Culture and Literature), 2013)
From the discussion above the poem from Heinrich Heine “Of Pearls and Stars” is about love from the writer for the girl that he love. As we know, Heinrich Heine is one of the poet who a romantic person. He also a person who concern about anything about love that happened in reality life someone. I analyze this poem “Of Pearls and Stars is tell us about love. The writer use imagery and symbol to represent what he feel when he is falling in love. He imagine what he feel with stars and pearls, because he want to show that his love is more worthly then pearls and stars that showed the writer that love is so pure. In short, the poem use imagery and symbol are to make the poem more beautiful, meaningful and has characteristic of the poem.